Development of organic production in Ukraine and Poltava region and prospect of it research - Чухліб, Ю. О. (Scientific Progress & Innovations, 2012)
Substantiated the necessity of greening agriculture to promote environmental preservation and production of safe food products and food raw materials. Given the definition of "organic farming" and described its main features. Review of literature regarding the status and trends of organic agriculture in Ukraine, particularly in the Poltava region. Defined basic problems of research in the organic production sphere in the coming years.